2014
DOI: 10.1111/maec.12124
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary urchins influence benthic community composition below the macroalgal zone

Abstract: Sea urchins are important ecosystem engineers in subtidal ecosystems worldwide, providing biogenic structure and altering nutrient dynamics through intensive grazing and drift algal capture. The current work evaluates red urchin (Strongylocentrotus franciscanus) density on fixed transects through time, individual displacement, and urchin‐associated benthic community composition using a field‐based approach at multiple depths (in and outside of the macroalgal zone) and replicated across sites in the San Juan Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 44 publications
0
19
0
7
Order By: Relevance
“…1). Red urchins can capture > 20 g drift algae urchin −1 d −1 in the San Juan Archipelago (Lowe et al 2014), an amount greater than they consumed in this study. The captured drift algae are composed of many species, among which Agarum is common, while Nereocystis is less frequently observed (Britton-Simmons et al 2009).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…1). Red urchins can capture > 20 g drift algae urchin −1 d −1 in the San Juan Archipelago (Lowe et al 2014), an amount greater than they consumed in this study. The captured drift algae are composed of many species, among which Agarum is common, while Nereocystis is less frequently observed (Britton-Simmons et al 2009).…”
Section: Discussionmentioning
confidence: 67%
“…Through wave action, tidal currents, and storms, drift algae are transported to neighboring ecosystems in both shallow photic and deep aphotic habitats (Duggins et al 1989, Krumhansl & Scheibling 2012a, where they support substantial secondary production and diversity (Vetter & Dayton 1998). This carbon subsidy from shallow to deep regions constitutes an essential food source for primary consumers and affects many aspects of ecosystem dynamics (Britton-Simmons et al 2009, Lowe et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we demonstrated that even though there were no significant differences in the FA profiles between algae consumed and egested, the urchins increased the nutritive quality of egesta in the form of increased total lipid content. This has significant implications for marine food webs, because increased lipid content in a food source is likely to benefit consumers, and suggests a mechanism for why macrophyte-derived carbon (generally) and kelpderived carbon (more specifically) may be a valuable trophic subsidy (Sauchyn and Scheibling, 2009;Sauchyn et al, 2011;Britton-Simmons et al, 2012;Lowe et al, 2015) to benthic organisms that might not otherwise utilize these sources directly.…”
Section: Discussionmentioning
confidence: 99%
“…This large kelp provides abundant food, including detrital material, to food webs within and below the photic zone ( Duggins & Eckman, 1994 ), as well as habitat and nursery space for a variety of fish species ( Carr, 1991 ). Red urchins playa smaller role in structuring these bull kelp forests than in many other habitats because of the high availability of drift kelp that limits their need to search for food ( Britton-Simmons, Foley & Okamoto, 2009 ; Lowe et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%